PEMANFAATAN LIMBAH TONGKOL JAGUNG SEBAGAI BIOPLASTIK DENGAN PENAMBAHAN VARIASI SILIKAT (SiO2) DAN SORBITOL - Setyawati, Harimbi; Alexander Marsen, Vinsen (jurnal ATMOSPHERE, 2025)
The issue of non-biodegradable plastic waste has driven the development of environmentally friendly bioplastics. This study aims to utilize corncob waste as a raw material for bioplastic production with the addition of varying amounts of silica (SiO₂) and sorbitol as a plasticizer. Corncobs were processed into starch and then mixed with sorbitol and silica in specific variations to produce bioplastics. The bioplastics were characterized by evaluating their thickness, tensile strength, elongation, biodegradability, and moisture content. The results showed that the addition of silica improved the mechanical strength of the bioplastic, while sorbitol enhanced its flexibility. The optimum formulation was obtained at specific concentrations of silica and sorbitol, producing bioplastics with physical and mechanical properties that meet biodegradable standards. In conclusion, corncob waste has potential as an environmentally friendly alternative material for bioplastics, with its quality further enhanced through the addition of silica and sorbitol.